Leadership in Educational Contexts in Finland Theoretical and Empirical Perspectives - Ahtiainen, Raisa; Hanhimäki, Eija; Leinonen, Jaana; Risku, Mika; Smeds-Nylund, Ann-Sofie (Educational Governance Research, 2024)
This open access book provides a comprehensive overview and in-depth coverage of contemporary aspects of leadership in the field of education in Finland. It brings together Finnish scholars to critically explore and discuss leadership in education in the context of the Finnish education system and in relation to international discourses around the topic. It discusses the phenomenon of leadership in educational contexts through several novel empirical and theoretical research designs. It includes themes such as distributed leadership and collaborative governance, changing aspects in the leadership profession, and contradictions in everyday organizational practices and realities. The work also combines conceptual discussions in educational and pedagogical leadership to analyze and to clarify the theoretical and conceptual multidimensionality and ambiguities.